Study of immobilized bovine and fish gelatin on carboxyl containing Polystyrene beads for Vero cell culture - Ahmad Nor, Yusilawati; Mel, Maizirwan; Mohd. Salleh, Hamzah; Ng, Kim Hooi; Wong, C. S. (Malaysian Medical Associations, 2010)

(untitled)
The aim of this study is to develop a polymeric microcarrier (MC) for obtaining a higher cell density of Vero cells in spinner vessel. Different types of gelatin; bovine (BG), fish (FG), cationized bovine (CBG) and cationized fish (CFG) were covalently immobilized on carboxyl group containing polystyrene (COOH-PS). Their performance was evaluated by the cell loading test in Vero cell culture as carrier system. It was found that Vero cell has better performance on BG with highest maximum cell number at 1.45x105 cell/ml with good microscopic and suspension ability; easy sampling and easy cell recovery.